FLASH CARD MEDIA UTILIZATION TO IMPROVE STUDENT ACTIVITY AND LEARNING OUTCOMES OF FAUNA DISTRIBUTION SUBTOPIC IN CLASS XI IPS I SMA XIN ZHONG SURABAYA - Felisia Ferra Ristanti; Fajar Arianto (Geosfera Indonesia, 2019)
The purpose of research to determine and describe whether the concept of flash card utilization is able to increase students activity students in learning in Geography subject. Though geography is a very important subject, particularly in determining the ample number of fauna found in Indonesia, which is even categorized as an endemic fauna. In addition, the manner in delivering subtopic which is considered monotonous by relying solely on reading books and summarizing what they have read are two things that are not surprising. Hence, those two facts encourage students not perform geography lessons enthusiastically. Considering the problems that occur, therefore I am interested in engaging the learning media "Flash Card" in delivering Subtopic of fauna distributions, especially in Indonesia. In each of these Flash Cards there is information regarding the fauna, starts from the picture, name, location of the distribution area, and animal characteristics. After performing the learning process engaging Flash Cards, students were divided into several groups and present Indonesia map along with regions name in front of the class. Then, the teacher would provide some questions related to the fauna characteristics and the groups were asked to answer questions by mentioning names and showing the origin of the fauna asked in the map. During this learning, students will likely compete againts other groups, but happened to be a pleasant circumstance without pressure. And at the end of the chapter, students will take a written test related to fauna distribution subtopic. The final result after applying the media "Flash Cards" turned out to be succeesful in improving student learning outcomes, especially upon fauna distribution subtopic in Indonesia at class XI IPS 1 SMA XinZhong Surabaya. As many as 28 students out of 36 students who did not accomplishminimum standard of 75 points, after engaging the media "Flash Card" they decreased up to only 3 students who did not meet the minimum criteria. Thereby, this result indicates that "Flash Card" mediautilization helps students to understand properly, embrace the subtopic adequately, and assist students to obtain better grades. Keywords: Geography Subject, Flash Card, pretest, posttest References Agung, A.A.Gede. (1998). Pengantar Evaluasi Pendidikan. Singaraja: STKIP Singaraja. Anggarwati, A. (2014). Pengaruh Make A Match Berbantuan Media Kartu Gambar Terhadap Hasil Belajar IPS SD.Jurnal (diterbitkan).Universitas Pendidikan Ganesha Astuti,W.(2013). Pengaruh Media Kartu Bergambar Terhadap Hasil Belajar Siswa Pada Materi Jamur di SMA.Jurnal (diterbitkan). Untan. Dimyati & Mudjiono. (2006). Hakikat Belajar dan Pembelajaran..Jakarta: Rineka Cipta Depdikbud.(1995). Metodik Khusus Pengajaran IPS di SekolahDasar. Jakarta: Depdikbud Handayani, F.(2009). Cooperative Learning Type Team Game Tournament (TGT) to increase the Learning Outcome of the Student of Class VII at SMP Negeri 1 PurwodadiPasuruan to Consept Kinds of Form the Earth Surface. Thesis, Geography Education Departement. Post Graduate Program, State University of Malang Hidayat, M, et al. (2008). Development of Geography Education in Elementary Schools. Jakarta: Ministry of National Education. Joni. (1984). Teaching and Learning Strategies. Jakarta: Ministry of Education and Culture Maghfiroh, (2013).Penggunaan Media Flashcard untukmeningkatkanhasilbelajar IPS padaPembelajarantematik di SekolahDasar.Surabaya : PGSD Unesa Ministry of Education and Culture.(1995). Special Methodology for Geography Teaching in Elementary Schools. Jakarta: Ministry of Education and Culture Mugiyanto.(2007). Penggunaan Kartu Konsep untuk Meningkatkan Hasil Pembelajaran Sejarah.Onlineat.http://jurnaljpi.wordpress.com/2007/ 11/14/mugiyanto.(2 Januari 2009). Noor, J. (2010). Metodelogi Penelitian. Jakarta: KencanaPrenada Media Group. Permana.(2015). Penerapan pembelajaran IPS dengan media ular tangga untuk meningkatkan minat belajar siswa. Kediri: Universitas Nusantara PGRI Kediri. Rohani, A. (1997). Media Instruksional Edukatif. Jakarta: Rineka Cipta. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License